Nutritional composition and antioxidant properties of calamansi (Citrus microcarpa) peels in different drying processes - KEZIA ESTHER T. ABAL; CASIANO H. CHORESCA JR.; FERNAND F. FAGUTAO; GWEN ANUEVO; MARY JANE S. APINES-AMAR; FERNIE A. CATIENZA; FIONA L. PEDROSO (Smujo International, 2024)
Abstract. Abal KET, Choresca Jr. CH, Fagutao FF, Anuevo G, Apines-Amar MJS, Catienza FA, Pedroso FL. 2024. Nutritional composition and antioxidant properties of calamansi (Citrus microcarpa) peels in different drying processes. Nusantara Bioscience 16: 292-296. Calamansi (Citrus microcarpa Bunge) is abundantly grown in the Philippines and is primarily utilized for its juice, resulting in peels as a waste product. This study aimed to evaluate the effects of different drying techniques (sun-drying, dehydration, and oven-drying) on the nutritional composition and antioxidant properties of calamansi peels. The dried samples were analyzed for nutritional content such as protein, fiber, fat, ash, carbohydrates, and moisture. Antioxidant properties were also measured through a DPPH scavenging activity assay, including total phenolic content and total flavonoid content. The results showed that Calamansi Dehydrated (CDD) had a significantly higher protein and fiber content than oven-dried and sundried, and calamansi oven-dried (COD) peels had the highest carbohydrate, fat, moisture, and ash content. Calamansi Sundried (CSD) has a significantly highest value of 21.04±2.44% scavenging activity, followed by CDD (20.79±5.43% scavenging activity), and then COD (8.91±1.89% scavenging activity) in DPPH assay. For Total Phenolic Content (TPC), CDD has a significantly higher value of 192.6±21.99 mg gallic acid equivalent (GAE) L-1 dry sample, followed by CSD and COD, with 145.7±6.54 mg GAE L-1 dry sample and 70.7±8.87 mg GAE L-1 dry sample, respectively. CSD had the highest value in Total Flavonoid Content (TFC) of 163.3±1.90 mg catechin equivalent (CE L-1 dry sample ) mg catechin Equivalent (CE) L-1 dry sample, followed by COD (121.0±6.87 mg CE L-1 sample), and CDD (41.9±6.25 mg CE L-1 sample. The findings suggest sun-drying and dehydration as drying techniques resulted in higher antioxidant properties and economic viability.